How Realistic is the GST ‘Promise Land’? Analyzing the Efficacy and Validity of GST Reform in India (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Goods and Services Tax (GST) is being touted as the “next logical and comprehensive indirect tax reform” that has been long overdue. With the GST Council scheduled to meet on 31st March 2017 to decide on ‘fitment rates’, administrative rules of GST etc. and the lower house of the Parliament having already passed the CGST, IGST, UGST and States Compensation Bills, this paper uses existing literature, media reports, PIB releases and the Gazette of India to understand the complex Indirect taxation structure of India and the changes to it brought about with the introduction of GST. Admittedly, there is a degree of vagueness associated with GST as of today but from a broad overall structure emerging from the 122nd Constitutional Amendment and the twelve meetings of GST council, an attempt has been made to critically analyze the efficacy or validity of the positive changes as well as the shortfalls associated with the ‘new regime’ which, though an improvement over its predecessor, leaves much more to be desired.